The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1985
DOI: 10.1210/jcem-60-5-1047
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Resistance, Acanthosis Nigricans, and Polycystic Ovaries Associated with a Circulating Inhibitor of Postbinding Insulin Action

Abstract: A 21-yr-old moderately obese woman with hirsutism, acanthosis nigricans, and oligomenorrhoea was diagnosed as having polycystic ovary syndrome. Despite hyperinsulinemia, binding of insulin to her red cells was within the range for normal, young adult subjects. Her serum did not bind or degrade [125I]insulin or alter its binding to fat cells, and was negative for insulin receptor antibodies. However, her serum caused a dose-dependent inhibition of insulin-stimulated lipogenesis (conversion of [3-3H]glucose to [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

1988
1988
2006
2006

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 18 publications
1
3
0
1
Order By: Relevance
“…At this dilution, the serum extract was equally effective in inhibiting insulin action at both maximal (25-ng/ml) and submaximal (0.75ng/ml) insulin concentrations (Table 1). These findings are similar to those reported by Harrison et al (9) in another patient with acanthosis nigricans and suggest that the serum contained a factor that inhibits insulin action. We also found that the serum extract blocked the stimulation of glucose transport produced either by hydrogen peroxide (Fig.…”
Section: 5supporting
confidence: 91%
See 1 more Smart Citation
“…At this dilution, the serum extract was equally effective in inhibiting insulin action at both maximal (25-ng/ml) and submaximal (0.75ng/ml) insulin concentrations (Table 1). These findings are similar to those reported by Harrison et al (9) in another patient with acanthosis nigricans and suggest that the serum contained a factor that inhibits insulin action. We also found that the serum extract blocked the stimulation of glucose transport produced either by hydrogen peroxide (Fig.…”
Section: 5supporting
confidence: 91%
“…Harrison et al (9) reported a young woman with insulin resistance, acanthosis nigricans, and polycystic ovary whose serum contained a low-molecular-weight substance that inhibited insulin action. They also reported that the substance was detectable in 77% of unselected patients with type II diabetes (10).…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, it is noteworthy that the hypothesized pathogenesis of polycystic ovary syndrome includes hyperinsulinemia or increased secretion of IGF-I (2) since patients with acromegaly usually show a high plasma IGF-I level and elevation of plasma IRI levels due to the presence of insulin resistance as in the present case. Association between polycystic ovary syndrome and insulin resistance (6) prompted the investigations of the potential role of insulin in ovarial function. It was reported that insulin alone or in synergism with LH stimulate ovarian androgen production (7-9) via the ovarian insulin receptor (10) or via intraovarian IGF system (1 1, 12).…”
Section: Discussionmentioning
confidence: 99%
“…Among them, insulin resistance, and compensatory hyperinsulinemia, are possibly the best known [5]. Aside from the association between PCOS and syndromes of extreme insulin resistance [3,20,21], growing evidence support the role for insulin resistance in the pathogenesis of hyperandrogenic disorders.…”
Section: Hyperandrogenism and Insulin Resis-tancementioning
confidence: 99%